2016
DOI: 10.1016/j.ecresq.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of household chaos in understanding relations between early poverty and children’s academic achievement

Abstract: The following prospective longitudinal study used an epidemiological sample (N = 1,236) to consider the potential mediating role of early cumulative household chaos (6–58 months) on associations between early family income poverty (6 months) and children's academic achievement in kindergarten. Two dimensions of household chaos, disorganization and instability, were examined as mediators. Results revealed that, in the presence of household disorganization (but not instability) and relevant covariates, income po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 46 publications
(91 reference statements)
2
53
0
1
Order By: Relevance
“…Further, although not explored in this study, future research could explore whether socioeconomic status moderates the impact of household chaos on adult attachment and parenting. Household chaos may exacerbate the effects of attachment in low‐income homes, where unpredictable and stressful living conditions are more likely than in higher income families (Garrett‐Peters et al, ). In the current study, our assessment of adult attachment did not include disorganized category, which is likely a risk factor for less sensitive and more intrusive parenting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although not explored in this study, future research could explore whether socioeconomic status moderates the impact of household chaos on adult attachment and parenting. Household chaos may exacerbate the effects of attachment in low‐income homes, where unpredictable and stressful living conditions are more likely than in higher income families (Garrett‐Peters et al, ). In the current study, our assessment of adult attachment did not include disorganized category, which is likely a risk factor for less sensitive and more intrusive parenting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Chaos is a description of contexts that are over‐stimulating because of environmental disorder (e.g., crowding, noise, clutter) or environmental instability (e.g., changes in housing, school, and family composition; Evans & Wachs, ; Shonkoff, ). Most studies that used the concept of chaos have focused on noise, clutter, and other types of disorder; a much smaller set included indicators of both disorder and instability (Coley, Lynch, & Kull, ; Garrett‐Peters, Mokrova, Vernon‐Feagans, Willoughby, & Pan, ; Raver et al, ; Vernon‐Feagans et al, ; Vernon‐Feagans, Willoughby, & Garrett‐Peters, ). Evidence has shown that disorganization, but not instability, mediates the relations between income and academic achievement (Garrett‐Peters et al, ) and predicts children's behavior at Kindergarten entry (Vernon‐Feagans et al, ).…”
Section: How Economic Instability Matters To Child Developmentmentioning
confidence: 99%
“…Most studies that used the concept of chaos have focused on noise, clutter, and other types of disorder; a much smaller set included indicators of both disorder and instability (Coley, Lynch, & Kull, ; Garrett‐Peters, Mokrova, Vernon‐Feagans, Willoughby, & Pan, ; Raver et al, ; Vernon‐Feagans et al, ; Vernon‐Feagans, Willoughby, & Garrett‐Peters, ). Evidence has shown that disorganization, but not instability, mediates the relations between income and academic achievement (Garrett‐Peters et al, ) and predicts children's behavior at Kindergarten entry (Vernon‐Feagans et al, ). Both disorder and instability early in life are associated with child physical and mental health issues (Coley et al, ).…”
Section: How Economic Instability Matters To Child Developmentmentioning
confidence: 99%
“…In addition to compromised health, Schmeer and Yoon () recently found that home environments that are kept in poor condition can constitute a significant source of psychosocial stress. Studies have also linked housing‐related risk factors to other developmental risks factors, including academic (Garrett‐Peters, Mokrova, Vernon‐Feagans, Willoughby & Pan, ; Lopoo & London, ) and neuropsychological (Pike et al., ) challenges—both of which are key predictors of delinquent behaviors (Jackson & Beaver, ; Maguin & Loeber, ). Given the associations between housing conditions and the physical, academic, and neuropsychological development of children, it is perhaps not surprising that housing conditions have also been linked to childhood behavioral problems.…”
Section: Introductionmentioning
confidence: 99%